Conexão entre fonte de sedimento e ambiente de deposição com base na assinatura química elementar - Andreoni, Leonardo Fonseca da Silveira (2017)
Erosive processes are harmful to the agriculture and the environment. Studies on sediment sources are important in order to evaluate the impacts generated and to point out possible solutions to solve it or to minimize the trouble generated. This work has been accomplished in order to study the soils and sediments of a hillslope where there is a tobacco culture. It is located in the Bácia do Arroio Boa Vista (Basin), Guamiranga – PR, in Brazil. The objective of this work was the identification of sediment sources along the hillslope and the evaluation of its connectivity with the riparian zone, correlating the location and depth of the samples with their chemical signature. Four soil and sediment profiles were sampled along the slope, four profiles along the riparian zone (two from the deposition site and two from the undisturbed, control site) and three surface samples were collected at the points of connection between these two sites. The profiles were collected at five depths: 0-10, 10-20, 20-30, 30-40 and 40-50cm. The analytical techniques applied were gamma spectrometry, to determine eU, eTh, K and 137Cs, and X-ray Fluorescence Spectrometry to determination of Fe, Ti, Ca, Mn, Zr and Sr. The measured concentration values are in agreement with typical values of these metals in soils. 137Cs were identified on surface of the control point, confirming that this zone has not been disturbed since the last global fallout of 137Cs that occurred in around 1964. In addition, the 137Cs were only detected in the 30 to 40 cm deep layer of the deposit, indicating that the sediments coming from the tobacco cultivation are mainly above the 30 cm deep. Some PCA's with the average values per depth and location were performed and interpreted together with the results of the 137Cs. Connection between hillslope and ripari zone it is observed on the PCA's as confirmed by the HCA's. The variables responsible for this response are: K, Mn, Sr, Ti e Zr, Th. Except for Ti, these elements have significant mobility. Samples of revolved soils are similar to each other and different from those of depth such that the stirring carried out on the slope does not reach. Although eU and eTh are present in the fertilizers administered in the soil of the slope, they are not useful tracers to establish connectivity between slope and riparian zone, but are responsible for grouping the soil samples revolved in the slope more pronounced than the other variables.